Prevalence and reasons for non‐nursing tasks as perceived by nurses: Findings from a large cross‐sectional study. (31st August 2021) - Grosso, Silvia; Longhini, Jessica; Tonet, Saverio; Bernard, Ines; Corso, Jacopo; de Marchi, Denis; Dorigo, Laura; Funes, Gianluca; Lussu, Massimo; Oppio, Nicolas; Grassetti, Luca; Pais Dei Mori, Luigi; et al.
Abstract: Aim: The aim of this study is to describe the prevalence and reasons for non‐nursing tasks as perceived by nurses. Background: Four types of non‐nursing tasks have been identified to date: (a) auxiliary; (b) administrative, (c) expected by allied health care professionals; and (d) medical. However, no studies on a large scale have been performed with the aim of identifying the prevalence of all of these non‐nursing tasks, and factors promoting or hindering their occurrence, given that they represent a clear waste of nurses' time. Methods: A cross‐sectional study in 2017, following The Strengthening the Reporting of Observational studies. All active nurses registered in an Italian provincial Nursing Board (=1331) willing to participate were involved. A questionnaire survey exploring the nature of the nursing tasks performed in daily practice and the underlying reasons was administered via paper/pencil and e‐mail. Results: A total of 733 nurses participated of which 94.5% performed at least one type of non‐nursing task, mainly administrative and auxiliary. Auxiliary tasks are less likely among nurses working in a community (odds ratio [OR] 0.43, 95% CI 0.29–0.63, p < .01) or in a residential (OR 0.41, 95% CI 0.23–0.72, p < .01) setting, in critical (OR 0.29, 95% CI 0.16–0.54, p < .01) or surgical (OR 0.37, 95% CI 0.19–0.75, p < .01) hospital settings, and when they deal with unexpected clinical events (OR 0.58, 95% CI 0.44–0.77, p < .01). Greater adequacy of nursing resources decreases the occurrence of auxiliary tasks (OR 0.98, 95% CI 0.97–0.99, p < .01), whereas the need to compensate for a lack of resources (OR 1.44, 95% CI 1.07–1.93, p < .01) increases it. Conclusions: Around one‐third of shift time is devoted to non‐nursing tasks; working in a hospital, in medical units, with lack of resources and with patients with predictable clinical conditions might increase the occurrence of auxiliary tasks. Implications for nursing management: Strategies to increase the time available for nursing care should consider the type of tasks performed by nurses, their antecedents and the value added to care in terms of patient' benefits.